Estudo da hidrólise de lactose por ß-galactosidase na forma livre e imobilizada - Tomás, Claudia Maria (1998)
The objective of this work was to study the kinetics of lactose hydrolysis using the enzyme galactosidase, in the free and immobilized form. The kinetic studies of the enzyme in the free and immobilized form were conducted in a micro reactor, at 30°C and pH of 6,5. The kinetic model found, for the free enzyme as well as the immobilized form, was the one of Michaelis-Menten. In the case of the free enzyme there was an inhibition by the galactose and the parameters found were Vm = 0,16 g/(Lmin), Km=17,04 g/L and Kj=54,26 g/L. The enzyme ß-galactosidase, when incubated at several pH values, presented better stability at pH 6,5. The optimum temperature was 40°C and the best pH was 6,5. The kinetics of hydrolysis of the lactose was studied in a range between 10 to 150g/L, inside the range of the lactose solubility. The enzymatic activity increased from 10 to llOg/L, and remained stable from this point on. Through a Central Composed Planning System it was possible to study the influence of three variables, temperature, concentration of lactose and pH jointly in the activity of the free enzyme. There was a strong influence of the pH that inhibited the effects of temperature and concentration. When studying the thermal stability of the free enzyme, it was noticed the influence of temperature by determining the time of half live. At 40°C the time of half life of the enzyme was 682,2 min and at 55°C, it was of 1,21 min. The immobilization of the lactase was accomplished using two different supports, an ionic exchange resin (Duolite) and a controlled pore silica (SPC). The enzyme immobilized on SPC had a maximum catalytic activity of l,49g/(g.L.min) and immobilized on Duolite of 0,84 g/(g.L.min).